MEASURING THE WELFARE GAIN FROM PERSONAL COMPUTERS. - GREENWOOD, JEREMY; KOPECKY, KAREN A. (Economic Inquiry, 2013)
The welfare gain to consumers from the introduction of personal computers (PCs) is estimated. A simple model of consumer demand is formulated that uses a slightly modified version of standard preferences. The modification permits marginal utility, and hence total utility, to be finite when the consumption of computers is zero. This implies that the good will not be consumed at a high enough price. It also bounds the consumer surplus derived from the product. The model is calibrated/estimated using standard national income and product account data. The welfare gain from the introduction of PCs is 2%-3% of consumption expenditure.